Don’t Judge a Book by Its Cover: A Case Study and Comparative Analysis of Popular vs. Academic Psychology Books - Katz, Debra Lynne (Journal of Scientific Exploration, 2022)
Many academic psychologists hold negative and stereotypical views about popular psychology books, even though there have been few formal investigations into these materials to understand their content, construction, purposes, or orientations, or their author’s credentials. This paper explores the origins of these views both within the Sociology of Scientific knowledge literature, and psychological literature. Through formal case study methodology, an extensive review and comparative analysis of books with the psychological construct of “Attention” in their title was undertaken to determine whether the current delineations between scholarly and popular materials and those who write them are as clear cut as those making such delineations seem to suggest, or if an alternative model of the relationship between academic and popular psychology literature could be offered. A bibliography of 145 books was compiled, followed by what turned out to be an arduous and at times impossible task of sorting these books into either popular vs. scholarly categories, revealing flaws in the dualistic nature of this activity that is often required of university students, instructors, and scholars alike. Six popular and six scholarly books (Table #3) revealed that while some of the popular books were less rigorous in referencing and representation of experimental or original findings, that they offered bibliotherapeutic benefits and were cited as often as scholarly materials in journal articles, books, and dissertations across multiple disciplines, thus suggesting that popularization is not simply a trickling down of knowledge from the scientific arenas to the public, but that science can be informed by professionals with expertise in applied areas. Meanwhile six books designated as scholarly only had a collective of 14 Amazon reader reviews. This project’s findings have implications for educators, researchers, librarians, and journal editors who may presently disqualify useful materials without fully understanding them, and for writers who could improve in their research and writing skills.